The moderating effect of firm size: Internationalization of small and medium enterprises (SMEs) in the manufacturing sector - Chelliah, S.; Pandian, S.; Sulaiman, Mohamed; Munusamy, J. (Academic Journals, 2010)
Previous research on the internationalization of small and medium enterprises (SMEs) explored the relationship between adoption of global orientation and competitive advantage, management attitude, and international knowledge and experience. However, there was a difference in opinion between those arguing that there is a positive relationship between these variables and others who contended that there is moderating effect of size on the internationalization. Within this context, this study sets out to further the discussion by comparing the global orientation of SMEs in Malaysia with their different level of size. In doing so, it draws upon the findings of survey of 300 internationalized enterprises located in northern region of Malaysia. The results suggest that size functions as moderating factor for internationalization only for relatively smaller firms. It has its biggest impact when relatively smaller SMEs acquire international knowledge and experience. They also note implications for managers and policy makers.